Genome-wide identification of bHLH transcription factors: Discovery of a candidate regulator related to flavonoid biosynthesis in Erigeron breviscapus - Gao, Qingqing; Song, Wanling; Li, Xia; Xiang, Chunfan; Chen, Geng; Xiang, Guisheng; Liu, Xiangyu; Zhang, Guanghui; Li, Xiaoning; Yang, Shengchao; Zhai, Chenxi; Zhao, Yan (Frontiers in Plant Science, 2022)
Erigeron breviscapus is a Compositae plant, and its rich flavonoids have shown strong preventative and curative effects in the treatment of cardio- and cerebrovascular diseases. bHLH genes play a crucial role in plant growth and development. There are 116 EbbHLH genes in E. breviscapus, and each gene has been named based on its chromosome location. Our phylogenetic analysis divided these genes into 19 subfamilies. To further investigate its function, EbbHLH80 was isolated from E. breviscapus leaves. Next, transcriptomic and metabolomic analyses of tobacco leaves were performed. Among 421 differentially accumulated compounds, 98 flavonoids were identified. In addition, differentially expressed genes were identified using RNA-seq, and further analysis suggested that EbbHLH80-OE could not only regulate the expression of some structural genes in the flavonoid biosynthesis pathway to achieve flavonoid accumulation but also be involved in the regulation of a series of downstream pathways, such as stress response, ABA and ethylene signal transduction, to affect plant growth and development. The results of our analysis provide new insights into the function of EbbHLH80 and lay the foundation for future functional studies on E. breviscapus.